1999
DOI: 10.1126/science.283.5398.55
|View full text |Cite
|
Sign up to set email alerts
|

DOAS Measurements of Tropospheric Bromine Oxide in Mid-Latitudes

Abstract: Episodes of elevated bromine oxide (BrO) concentration are known to occur at high latitudes in the Arctic boundary layer and to lead to catalytic destruction of ozone at those latitudes; these events have not been observed at lower latitudes. With the use of differential optical absorption spectroscopy (DOAS), locally high BrO concentrations were observed at mid-latitudes at the Dead Sea, Israel, during spring 1997. Mixing ratios peaked daily at around 80 parts per trillion around noon and were correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 17 publications
8
147
1
Order By: Relevance
“…It is noticeable that most of the enhanced periods of BrO also coincide with enhanced light paths, this is indicative of the increased aerosol arriving from the sea. Away from polar regions and those with high salt levels 38 there is growing evidence from aerosol measurements of the widespread prevalence of the bromine explosion mechanism over oceanic areas. 42 Beyond boundary layer BrO production from the explosion mechanism, there is growing evidence that BrO may pervade throughout the free troposphere at the 0.6-2 pptv level 52,55 having implications for the global oxidation capacity.…”
Section: Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable that most of the enhanced periods of BrO also coincide with enhanced light paths, this is indicative of the increased aerosol arriving from the sea. Away from polar regions and those with high salt levels 38 there is growing evidence from aerosol measurements of the widespread prevalence of the bromine explosion mechanism over oceanic areas. 42 Beyond boundary layer BrO production from the explosion mechanism, there is growing evidence that BrO may pervade throughout the free troposphere at the 0.6-2 pptv level 52,55 having implications for the global oxidation capacity.…”
Section: Experimental Evidencementioning
confidence: 99%
“…38 The major source of gas-phase bromine in the lower troposphere is thought to be the release of species such as IBr, ICl, Br 2 and BrCl from sea-salt aerosol, following the uptake from the gas-phase and subsequent reactions of hypohalous acids (HOX, where X 5 Br, Cl, I). 39 The halogen release mechanism is autocatalytic 37 and has become known as the ''Bromine explosion''.…”
Section: Halogen Radicals (Xo Oxo)mentioning
confidence: 99%
“…Although more localized, inorganic bromine emissions have also been identified over salt lakes (Hebestreit et al, 1999), in the marine boundary layer (Leser et al, 2003;SaizLopez et al, 2004;Read et al, 2008) and in volcanic plumes (Bobrowski et al, 2003;Oppenheimer et al, 2006;Theys et al, 2009a). Observations from space (e.g., Richter et al, 2002;Van Roozendael et al, 2002), ground-based Theys et al, 2007) and balloon-borne (Harder et al, 1998;Fitzenberger et al, 2000) instruments have shown that inorganic bromine may be produced and sustained in the free troposphere at the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…But still, direct measurements of BrO in the mid-latitude troposphere are rare. Hebestreit et al [1999] reported BrO up to 80 parts per trillion (ppt) in the Dead Sea valley and Wagner et al [2001] found BrO at the Caspian Sea using GOME satellite data. Bromide from sea salt deposits is most likely the origin of reactive bromine in this case ('Bromine Explosion' [Platt and Lehrer, 1997;Vogt et al, 1996]).…”
Section: Introductionmentioning
confidence: 99%